2021
DOI: 10.1002/smll.202103484
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Selective Etching of Twinned Graphene on Liquid Copper Surface

Abstract: requires only two parameters: the lattice misalignment angle (θ) between the two single-crystalline grains and the alignment angle (φ) of the GB. It is well documented that GBs greatly affect the electronic, [1][2][3][4][5][6] mechanical, [7][8][9], and thermal properties [5,[10][11][12] of a 2D material, and therefore, GB engineering during 2D materials synthesis and processing is critical for applications. The study of TBs in 3D material is of great interest because of the dominance of TBs in 3D materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…We demonstrate that the shape of the graphene nanospear can be tuned by varying the experimental condition. By increasing the H 2 /CH 4 ratio, which has previously been shown to facilitate the etching of graphene and slow down the VSS growth rate, [ 7d,24 ] we have successfully synthesized very sharp GNSs, comprising of a central GNR ( Figure a,b; Figure S5, Supporting Information). The SEM images of a typical GNS with a tip angle of 10° is shown in Figure 3c,d.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate that the shape of the graphene nanospear can be tuned by varying the experimental condition. By increasing the H 2 /CH 4 ratio, which has previously been shown to facilitate the etching of graphene and slow down the VSS growth rate, [ 7d,24 ] we have successfully synthesized very sharp GNSs, comprising of a central GNR ( Figure a,b; Figure S5, Supporting Information). The SEM images of a typical GNS with a tip angle of 10° is shown in Figure 3c,d.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Liu et al demonstrated the selective etching of graphene twin boundaries by hydrogen. [121] The etching of graphene twin boundaries depended on the formation energy of each boundary (Figure 15c). In contrast, the single crystal graphene films were etched with randomly distributed hexagonal holes with the same alignment direction (Figure 15d).…”
Section: Step Edge-guided Epitaxial Growth On High-index Substratesmentioning
confidence: 99%
“…The etched holes are along a straight line or grain boundaries; etched GBs (marked by blue arrows) and intact GBs (marked by red arrows). Adapted with permission [121]. Copyright 2021, Wiley-VCH GmbH.…”
mentioning
confidence: 99%
“…[12][13][14] However, due to a small angle misalignment of the oriented GIs under the coalescence process, there inevitably formed the polygonal GIs beyond the hexagonal structure, which exhibited the variousshaped geometric structures and the novel physical properties. [15][16][17][18][19][20][21] Geng et al reported the synthesis of polygonal GIs from seven-to twelve-pointed GIs on liquid Cu substrate by CVD method. [15] A similar phenomenon has also been observed on both liquid and solid Cu substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Recently, Liu et al successfully elucidated the selective etching of GBs by H 2 in twinned graphene grown on liquid Cu. [20] In addition, Ahn et al established a dodecagonal quasicrystal structure based on the twisted bilayer graphene by exactly 30°to realize the nonrelativistic fermions. [21] However, a facile characterization and deeper understanding of the formation mechanism of GBs in the polygonal GIs grown on solid Cu surface are of great challenge.…”
Section: Introductionmentioning
confidence: 99%